1968
DOI: 10.1002/bit.260100303
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of RNA to 5′‐nucleotide by seed sprouts, particularly malt sprouts

Abstract: SummaryConditions for the efficient conversion of commercial RNA to nucleoside 5'-monophosphate by means of a phosphodiesterase in malt sprouts have been determined. A comparison of the enzyme content of the rootlets, stems, and kernels of various plant seedlings, including barley, rye, oat, wheat, rice, and beans shows maximum amounts in the rootlets, and minimum quantities in the ungerminated kernels. Of all the seedlings tested, (mung bean, soy bean, oat, wheat, rice, barley) barley gave the highest convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…25 The results showed that the MSG, 5′-GMP and 5′-IMP components identified by HPLC were found in eb-RPH and ep-RPH (Fig. 26 The proteolytic process could break down these nucleotides that are bound to the proteins, resulting in the release of non-volatile flavor compounds. The MSG, 5′-GMP and 5′-IMP found in the two RPHs could be naturally synthesized and are present in brown rice.…”
Section: Biofunctional Properties Of the Brown Rice Protein Hydrolysatementioning
confidence: 99%
See 1 more Smart Citation
“…25 The results showed that the MSG, 5′-GMP and 5′-IMP components identified by HPLC were found in eb-RPH and ep-RPH (Fig. 26 The proteolytic process could break down these nucleotides that are bound to the proteins, resulting in the release of non-volatile flavor compounds. The MSG, 5′-GMP and 5′-IMP found in the two RPHs could be naturally synthesized and are present in brown rice.…”
Section: Biofunctional Properties Of the Brown Rice Protein Hydrolysatementioning
confidence: 99%
“…The MSG, 5′-GMP and 5′-IMP found in the two RPHs could be naturally synthesized and are present in brown rice. 26 The proteolytic process could break down these nucleotides that are bound to the proteins, resulting in the release of non-volatile flavor compounds. Therefore, the MSG, 5′-GMP and 5′-IMP contents in ep-RPH were higher than those in eb-RPH because of the high hydrolysis efficiency of PROTEASE FP51®.…”
Section: Biofunctional Properties Of the Brown Rice Protein Hydrolysatementioning
confidence: 99%
“…5 -phosphodiesterase (5 PDE) has been the predominant enzyme isolated and utilised in applications from barley rootlets. It has been found in appreciable amounts in the barley rootlets and in the malted barley grain [71,72]. The enzyme has been used commercially to hydrolyse RNA to make 5 -nucleotides.…”
Section: Enzyme Applicationsmentioning
confidence: 99%
“…Processes for the extraction of 5 PDE from barley rootlets vary, with some patents (Table 4) also developed. The process generally requires a purification step, because various other undesired enzymes such as phosphatases, 5 -nucleotidase and nucleosidases may also be present in barley rootlets [71,78] that may produce unwanted products or inhibit 5 -nucleotide yield.…”
Section: Enzyme Applicationsmentioning
confidence: 99%
“…Reported enzymes extracted from barley roots included DNase, RNase, 5'-adenosine monophosphatase, 3'-uridine monophophatase, and other nucleases [7,9,10]. Laufer and Gutcho [11] reported that 5'-nucleotides, 3'-nucleotides, phosphoric acid and nitrogenous bases were found in the enzymatic hydrolysis products of yeast RNA by enzymes from barley roots. As we know, the main hydrolysis products of yeast RNA catalyzed by 5'-PDE are 5'-nucleotides, mainly 5'-CMP, 5'-UMP, 5'-GMP and 5'-AMP, it is more reasonable to appraise the enzyme activity of 5'-PDE by measuring the amount of the four 5'-nucleotides in the hydrolysis reaction, to detect a more reliable and precise enzyme activity.…”
Section: Introductionmentioning
confidence: 99%